Autoinducer‐2‐mediated quorum‐sensing system resists T4 phage infection in Escherichia coli. (15th November 2021) - Ding, Yafang; Zhang, Dongfang; Zhao, Xiaoman; Tan, Wenzhang; Zheng, Xiaodan; Zhang, Qi; Ji, Xiuling; Wei, Yunlin
Abstract: In response to the restriction of nutrients and predation by natural enemies, bacteria have evolved complex coping strategies to ensure the reproduction and survival of individual species. Quorum sensing (QS) is involved in the bacterial response to phage predation and regulation of cellular metabolism. However, to date, no clear evidence exists regarding the involvement of autoinducer‐2 (AI‐2)‐mediated QS systems in Escherichia coli in response to the challenges of nutrient restriction and phage infection. In this study, the role of the AI‐2‐mediated QS system in resisting T4 phage infection and regulating cell mechanisms in E. coli was revealed for the first time. This effect of the AI‐2‐mediated QS was achieved by simultaneously downregulating the T4 absorption site and carbon and glucose metabolism. Additionally, we found that lsrB, a metabolic brake, participates in AI‐2‐mediated regulation and maintenance of the normal metabolic balance of cells. The novel phage defense strategy and regulation and maintenance of cellular metabolism effectively limited the expansion of the phage population.